The Effectiveness of Islamic Education Learning with Creative Worksheets through the Application of Quipper with Facebook Account - St. Wardah Hanafie Das; Abdul Halik; Besse Tuti Herlin (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
This study aims to determine the significance differences by those who are taught using Quipper through a facebook account in assigning creative worksheets and those who are not taught using Quipper in the field of Islamic education studies. This research method is an experiment with Quasi Nonequivalent control group design. The population was 70 people and the sample was divided into experiment class and control class with a total of 35 people each. The research instrument was the Observation Sheet, Student Learning Outcomes Test in the form of worksheets, questionnaires, study documents, and triangulation. Quantitative data analysis with descriptive and inferential non-parametric statistical techniques Mann Whitney U-Test test. Data analysis was assisted by SPSS application version 24. The results of the study were the use of Quipper School through a Facebook account in assigning creative worksheets to improve the effectiveness of Islamic education learning in SMK Negeri 1 Sengkang meeting the KKM, and there were significant differences between use and not use Quipper School through facebook account in assigning creative worksheets, and in the mann-whitney test, it is known the value of Asymp. Sig. (2- tailed) of 0,000 is smaller than probability value of 0.05 then the hypothesis H0 is rejected H1 is accepted. The next important study is the development of Quipper School media through a Facebook account on strengthening psychomotor competence in the field of Islamic education studies.